(untitled) (Latakia University Journal -Biological Sciences Series, 2024)
This research was conducted to study the effect of four biochar rates (0-100-300-600 Kg. dunum-1) in soil physical characteristics and soybean productivity growing in a loamy soil. The study showed a significant decrease in the bulk density of the loamy studied soil in both depths (0-20 and 20-40 cm) with increasing biochar rates compared to the control. Generally, soil total porosity increased significantly in both depths with increasing biochar rates reaching the highest value at a rate of 600 kg. dunum -1 with increments of 7.25% and 9.47% respectively compared to the control. The pores containing available water (0.2-10 μm) for depth (0-20 cm) rose with increasing biochar supply to 300 and 600 kg. dunum-1 significantly by 2.09%, 4.38% and by 2, 3.58% for depth (20-40cm) in comparison with the control. Soil’s experimental constants (a and b) increased in both soil depths (0-20 and 20-40cm) with increasing biochar amendment rates causing improvement in waster movement and its absorption by plant. The improvement in soil physical properties caused increasing soybean productivity markedly after biochar supply (100-300-600 kg. dunum-1) by (8.2-25.3-33.85%) as a percentage control respectively.